Control of Néel-type Magnetic Kinks Confined in a Square Nanostructure by Spin-Polarized Currents - Chen, Ji-Pei; Lin, Jia-Qiang; Song, Xiao; Chen, Yuan; Chen, Zhi-Feng; Li, Wen-An; Qin, Ming-Hui; Hou, Zhi-Peng; Gao, Xing-Sen; Liu, Jun-Ming (Frontiers in Physics, 2021)
Magnetic skyrmion in chiral magnet exhibits a variety of unique topological properties associated with its innate topological structure. This inspires a number of ongoing searching for new topological magnetic textures. In this work, we used micromagnetic simulations and Monte Carlo simulations to investigate an exotic Néel-type magnetic kinks in square-shaped nanostructures of chiral magnets, which performs rather stably in the absence of magnetic field. The individual magnetic kink can reside in one of the four possible corners, and carry possibly upward or downward core polarity, constituting eight degenerate states. In addition, these kinks also exhibit unique behaviors of generation, stability and dynamics, as revealed by micromagnetic simulations. It was found that such kinks can be created, annihilated, displaced, and polarity-reversed on demand by applying a spin-polarized current pulse, and are easily switchable among the eight degenerate states. In particularly, the kinks can be switched toward the ferromagnetic-like states and backward reversibly by applying two successive current pulses, indicating the capability of writing and deleting the kink structures. These findings predict the existence of Néel-type magnetic kinks in the square-shaped nanostructures, as well as provide us a promising approach to tailor the kinks by utilizing the corners of the nanostructures, and control these states by spin-polarized currents. The present work also suggests a theoretical guide to explore other chiral magnetic textures in nanostructures of polygon geometries.